2011
DOI: 10.1002/cncr.26479
|View full text |Cite
|
Sign up to set email alerts
|

Racial and regional disparities in lung cancer incidence

Abstract: (SEER) were used for this study; representing 100% of the US population. Age-adjusted incidence rates and 95% confidence intervals for demographic (age, sex, race, ethnicity, and US Census region), and tumor (stage, grade, and histology) characteristics were calculated. RESULTS: During 2004 to 2006, 623,388 people (overall rate of 68.9 per 100,000) were diagnosed with lung cancer in the US. Lung cancer incidence rates were highest among men (86.2), Blacks (73.0), persons aged 70 to 79 years (431.1), and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 43 publications
(57 reference statements)
1
52
0
Order By: Relevance
“…Asians were classified as nonminority because their results did not differ significantly from those of whites. Patients were grouped according to the tumor, node, metastasis staging criteria on the basis of reviews of medical records (11). Comorbidity information (chronic obstructive pulmonary disease, asthma, heart disease, diabetes, renal disease, liver disease, and depression) was collected by self-report and chart review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asians were classified as nonminority because their results did not differ significantly from those of whites. Patients were grouped according to the tumor, node, metastasis staging criteria on the basis of reviews of medical records (11). Comorbidity information (chronic obstructive pulmonary disease, asthma, heart disease, diabetes, renal disease, liver disease, and depression) was collected by self-report and chart review.…”
Section: Methodsmentioning
confidence: 99%
“…Provider-related factors such as limited cultural sensitivity, stereotyping, and worse patient-physician communication may also be involved, but supporting evidence regarding these aspects of care is limited (10). Even after controlling for these factors (4,11,12), however, treatment disparities persist, suggesting that patient-level factors, which might be culturally related, may also contribute to lung cancer differences.…”
mentioning
confidence: 99%
“…Lung cancer is one of the most common causes of cancerrelated death and is a malignancy with high incidence worldwide [1]. Approximately 80 % of all lung cancers are diagnosed histologically as non-small cell lung cancer (NSCLC), and at the time of diagnosis, a high proportion of patients already suffer from metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported racial disparities in the incidence and mortality of lung cancer in the United States [10][11][12][13]. Black patients with lung cancer are diagnosed at a younger age and with more advanced disease and experience greater mortality than white patients with lung cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%